Purification and Characterization of Hemagglutinating Proteins from Poker-Chip Venus (Meretrix lusoria) and Corbicula Clam (Corbicula fluminea). (1st May 2012) - Cheng, Chin-Fu; Hung, Shao-Wen; Chang, Yung-Chung; Chen, Ming-Hui; Chang, Chen-Hsuan; Tsou, Li-Tse; Tu, Ching-Yu; Lin, Yu-Hsing; Liu, Pan-Chen; Lin, Shiun-Long; Wang, Way-Shyan
Abstract : Hemagglutinating proteins (HAPs) were purified from Poker-chip Venus ( Meretrix lusoria ) and Corbicula clam ( Corbicula fluminea ) using gel-filtration chromatography on a Sephacryl S-300 column. The molecular weights of the HAPs obtained from Poker-chip Venus and Corbicula clam were 358 kDa and 380 kDa, respectively. Purified HAP from Poker-chip Venus yielded two subunits with molecular weights of 26 kDa and 29 kDa. However, only one HAP subunit was purified from Corbicula clam, and its molecular weight was 32 kDa. The two Poker-chip Venus HAPs possessed hemagglutinating ability (HAA) for erythrocytes of some vertebrate animal species, especially tilapia. Moreover, HAA of the HAP purified from Poker-chip Venus was higher than that of the HAP of Corbicula clam. Furthermore, Poker-chip Venus HAPs possessed better HAA at a pH higher than 7.0. When the temperature was at 4°C–10°C or the salinity was less than 0.5‰, the two Poker-chip Venus HAPs possessed better HAA compared with that of Corbicula clam.